I Borghi di fondazione della riforma agraria pugliese. Il linguaggio della cittÃ rurale, fra tradizione e innovazione (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
The aim of the dissertation is to investigate the relationships between settling phenomena and building phenomena, typical of the villages of the Foundation born in the Apulian dauna during the Fascist period. This is one of the areas related to the great work of the Land Reform, destined to become a laboratory for experimentation with new languages ​​and the iconography of the Other Italian Modernity. The daunio territory - our specific field of investigation - is located in the Tavoliere delle Puglie. In the center, the remains of the ancient Roman colony of Herdonia (today's Ordona) are today surrounded by small towns built in the late Middle Ages due to the enormous production capacity of its plain. This was the reason why, in the 17th century, the Bourbon government started the first reclamation work, supporting it with the creation of five new villages, called Cinque Reali Siti. Developed along the Via Consolare route (Strada Regia) they vast agricultural area with its own legislation and having as main center of government, the village of Orta Nova. It was a Plan that anticipated in large part what was then expanded in fact, during the Fascist Ventennio with the Grande Bonifica della Capitanata, destined to give life to new forms of settlement useful for the new agricultural colonization. Programmatically "anti-metropolitan", they would have had the shape and the "minimal" dimension of the rural villages, as well as a strategic location in the territory such as to constitute them as an organic whole of "morphological multiples" belonging to a single settlement code. This was a first, embryonic hypothesis of city-territory; a multicentric territory, with an aesthetic code derived from the transformation of the autochthonous characters of rural buildings, into those of rural Rationalism meanwhile experimented in the Pontine Plain. Extending these considerations to today's problems, the analysis aims to make a critical contribution not only to the historical knowledge of those processes, but also to the construction of a contemporary city capable of re-establishing itself with an urban form. Using a reflection by Ludovico Quaroni, the objective of this instance is therefore to "take back the thread of a discourse, an action for the shape of the city", a new city understood as the result of a process of critical self-awareness that finds in the planning action the cultural and technical reflection of the collective work, the communicative aesthetics of its social anthropology."A civilization capable of overthrowing [...] the traditional accumulation of spontaneous urbanism [...] is also able to preserve project capacity once the city is built. It is far-sighted because it knows how to plan its own future. It raises rivers, builds huge elevated platforms to keep the whole city dry, regulates the black and white urban waters, produces, masses and distributes food, builds beautiful buildings for the common activity of its members, possesses sufficient authority to manage all this and make it "last a long time". (Mortimer Wheeler)